Reduction of nitroaromatic compounds by anaerobic bacteria isolated from the human gastrointestinal tract. - Rafil, F (1991)
Human intestinal microbial flora were screened for their abilities to reduce nitroaromatic compounds by growing them on brain heart infusion agar plates containing 1-nitropyrene. Bacteria metabolizing 1-nitropyrene, detected by the appearance of clear zones around the colonies, were identified as Clostridium leptum, Clostridium paraputrificum, Clostridium clostridiiforme, another Clostridium sp., and a Eubacterium sp. These bacteria produced aromatic amines from nitroaromatic compounds, as shown by thin-layer chromatography, high-pressure liquid chromatography, and biochemical tests. Incubation of three of these bacteria with 1-nitropyrene, 1,3-dinitropyrene, and 1,6-dinitropyrene inactivated the direct-acting mutagenicity associated with these compounds. Menadione and o-iodosobenzoic acid inhibited nitroreductase activity in all of the isolates, indicating the involvement of sulfhydryl groups in the active site of the enzyme. The optimum pH for nitroreductase activity was 8.0. Only the Clostridium sp. required added flavin adenine dinucleotide for nitroreductase activity. The nitroreductases were constitutive and extracellular. An activity stain for the detection of nitroreductase on anaerobic native polyacrylamide gels was developed. This activity stain revealed only one isozyme in each bacterium but showed that the nitroreductases from different bacteria had distinct electrophoretic mobilities.